LISTA RECENZTÓW ROCZNIKA 2012: - Studia Psychologica, Redakcja (Studia Psychologica: Theoria et praxis, 2018)
Dr Anna Batory Dr Dariusz Buksik Dr Michał Chruszczewski Dr Jan Cieciuch Dr Krzysztof Fronczyk Dr hab. Zbigniew Gaś Dr hab. Alicja Głębocka Dr hab. Paweł Izdebski Dr hab. Ewa Jackowska Dr hab. Iwona Janicka Dr hab. Romuald Jaworski Dr Dariusz Krok Prof. dr hab. Maria Lis-Turlejska Dr hab. Maria Ledzińska Prof. dr hab. Maria Lewicka Dr hab. Hanna Liberska Dr hab. Zdzisław Majchrzyk Dr Katarzyna Martowska Prof. dr hab. Jolanta Miluska Dr Marek Nieznański Prof. dr hab. Władysław Paluchowski Dr hab. Andrzej Pankalla Dr Joanna Piekarska Dr hab. Barbara Pilecka Prof. dr hab. Władysława Pilecka Prof. dr hab. Mieczysław Plopa Dr Joanna Radoszewska Dr hab. Maria Ryś Prof. dr hab. Ryszard Stachowski Dr hab. Elżbieta Stojanowska Dr hab. Maria Straś-Romanowska Dr Włodzimierz Strus Dr Sławomir Ślaski Dr hab. Jacek Śliwak Prof. dr hab. Janusz Trempała Dr hab. Barbara Tryjarska Dr Monika Włodarczyk-Dudka